An interlaboratory comparison study on the measurement of elements in PM10. (January 2016) - Yatkin, Sinan; Belis, Claudio A.; Gerboles, Michel; Calzolai, Giulia; Lucarelli, Franco; Cavalli, Fabrizia; Trzepla, Krystyna
Abstract: An inter-laboratory comparison study was conducted to measure elemental loadings on PM10 samples, collected in Ispra, a regional background/rural site in Italy, using three different XRF (X-ray Fluorescence) methods, namely Epsilon 5 by linear calibration, Quant'X by the standardless analysis, and PIXE (Particle Induced X-ray Emission) with linear calibration. A subset of samples was also analyzed by ICP-MS (Inductively Coupled Plasma-Mass Spectrometry). Several metrics including method detection limits (MDLs), precision, bias from a NIST standard reference material (SRM 2783) quoted values, relative absolute difference, orthogonal regression and the ratio of the absolute difference between the methods to claimed uncertainty were used to compare the laboratories. The MDLs were found to be comparable for many elements. Precision estimates were less than 10% for the majority of the elements. Absolute biases from SRM 2783 remained less than 20% for the majority of certified elements. The regression results of PM10 samples showed that the three XRF laboratories measured very similar mass loadings for S, K, Ti, Mn, Fe, Cu, Br, Sr and Pb with slopes within 20% of unity. The ICP-MS results confirmed the agreement and discrepancies between XRF laboratories for Al, K, Ca, Ti, V, Cu, Sr and Pb. The ICP-MS results are inconsistent with the XRF laboratories for Fe and Zn. The absolute differences between the XRF laboratories generally remained within their claimed uncertainties, showing a pattern generally consistent with the orthogonal regression results. Highlights: Interlab comparison of XRF and ICP-MS labs was conducted to measure elements in PM10 . XRF labs are comparable for S, K, Ti, Mn, Fe, Cu, Br, Sr and Pb. ICP-MS confirmed XRF-interlab comparability of Al, K, Ca, Ti, V, Fe, Cu, Sr and Pb. ICP-MS results are inconsistent with the XRF laboratories for Fe and Zn.